Pendidikan Jiwa dalam Perspektif Ibnul Qayyim al-Jauziyyah - Muhammad Aidil Akbar; Siti Rohimah (TSAQOFAH, 2026)
Education of the soul is an important aspect of Islamic character formation because it is related to the purification, control, and development of human inner potential. This study examines the concept of education of the soul in the thought of Ibnul Qayyim Al-Jauziyyah and its relevance to character education in the contemporary era. This study used a library research method with a content analysis approach to the primary works of Ibnul Qayyim Al-Jauziyyah, particularly Madarijus Salikin and Ighatsatul Lahfan, as well as relevant secondary literature. The results of the study show that the concept of education of the soul according to Ibnul Qayyim Al-Jauziyyah rests on three main pillars, namely a deep understanding of the nature of the soul or nafs and its hierarchy, recognition of the diseases of the soul and their root causes, and methods of soul purification or tazkiyatun nufus, which include muhasabah, muraqabah, mujahadah, and sincere repentance. These findings indicate that Ibnul Qayyim Al-Jauziyyah’s approach to education of the soul is not only spiritual-normative but also psychological and practical. The conclusion of this study affirms that the concept of education of the soul in the thought of Ibnul Qayyim Al-Jauziyyah is relevant for adaptation within the framework of Islamic character education in modern educational institutions, including pesantren and madrasahs. The implications of this study provide a conceptual contribution to the development of character education based on soul purification and serve as a foundation for strengthening Islamic educational practices oriented toward the spiritual, moral, and psychological development of students.